2008
DOI: 10.1093/cercor/bhm218
|View full text |Cite
|
Sign up to set email alerts
|

Stages of Motor Output Reorganization after Hemispheric Stroke Suggested by Longitudinal Studies of Cortical Physiology

Abstract: Reorganization of motor circuits in the cerebral cortex is thought to contribute to recovery following stroke. These can be examined with transcranial magnetic stimulation (TMS) using measures of corticospinal tract integrity and intracortical excitability. However, little is known about how these changes develop during the important early period post-stroke and their influence on recovery. We used TMS to obtain multiple measures bilaterally in a group of 10 patients during the early days and weeks and up to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
227
5
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 271 publications
(255 citation statements)
references
References 57 publications
18
227
5
5
Order By: Relevance
“…Recent animal data also showed changes in cortical excitability after small cortical lesions associated with functional recovery. In humans, enhanced resting motor cortical excitability (or reduced inhibition) has been proposed as a possible contributing mechanism 18 to the recovery process, 14,31 possibly influenced by interactions with secondary motor areas, such as the premotor cortex or the supplementary motor area 32,33 or even with homologous areas of the opposite hemisphere. 27,28 Because motor deficits in patients are most pronounced while performing a motor task, we hypothesized that abnormalities in intracortical function might manifest themselves more prominently in the premovement period, when patients intend to move the paretic hand.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent animal data also showed changes in cortical excitability after small cortical lesions associated with functional recovery. In humans, enhanced resting motor cortical excitability (or reduced inhibition) has been proposed as a possible contributing mechanism 18 to the recovery process, 14,31 possibly influenced by interactions with secondary motor areas, such as the premotor cortex or the supplementary motor area 32,33 or even with homologous areas of the opposite hemisphere. 27,28 Because motor deficits in patients are most pronounced while performing a motor task, we hypothesized that abnormalities in intracortical function might manifest themselves more prominently in the premovement period, when patients intend to move the paretic hand.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in patients with dystonia, premovement SICI and SICI at rest showed substantially different effects with reduction in SICI at rest and persistent lack of modulation of SICI during movement preparation. 7 Previous studies evaluating motor cortex excitability in the acute and subacute stages after stroke 1,3,[13][14][15][16][17][18] showed decreased resting SICI in the ipsilesional M1, an abnormality that may normalize in the chronic stage. 15,[17][18][19] Movement-related changes in SICI in stroke patients intending to move the paretic hand have not been investigated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This interhemispheric asymmetry has been reported to be greatest in the acute stage, after which it begins to recover [3,30]. Recovery from stroke is based at least partly on the reorganization of the surviving parts of the brain and rebuilding of functional networks [23,26].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle spasticity may be related to changes in peripheral tissues and the breakdown of the central nervous system in acute stroke patients 15,16 , and a model of spasticity development for the stages of motor output reorganization after stroke has been proposed spasticity is considered to be a manifestation of maladaptive plastic responses 17 . Studies have shown the effects of…”
Section: Discussionmentioning
confidence: 99%